2015
DOI: 10.1002/jhm.2329
|View full text |Cite
|
Sign up to set email alerts
|

Association of clinical practice guidelines with emergency department management of febrile infants ≤56 days of age

Abstract: Background Differences among febrile infant institutional clinical practice guidelines (CPGs) may contribute to practice variation and increase healthcare costs. Objective Determine the association between pediatric emergency department (ED) CPGs and laboratory testing, hospitalization, ceftriaxone use, and costs in febrile infants. Design Retrospective cross-sectional study in 2013. Setting Thirty-three hospitals in the Pediatric Health Information System. Patients Infants ≤ 56 days with a diagnosis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
80
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 65 publications
(83 citation statements)
references
References 28 publications
3
80
0
Order By: Relevance
“…29 Similar to previous work, we observed a significantly higher admission rate for older infants with a traumatic LP compared to those without. 2 Our CSF WBC count correction factor would allow almost 600 additional infants age 29–60 days without bacterial meningitis to be appropriately classified as not having CSF pleocytosis for every misclassified case of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 91%
“…29 Similar to previous work, we observed a significantly higher admission rate for older infants with a traumatic LP compared to those without. 2 Our CSF WBC count correction factor would allow almost 600 additional infants age 29–60 days without bacterial meningitis to be appropriately classified as not having CSF pleocytosis for every misclassified case of bacterial meningitis.…”
Section: Discussionsupporting
confidence: 91%
“…First, prior investigations each were conducted at a single center, where clinical care could have been more determined by protocol. 23 Our study demonstrates the impact of a positive EV PCR test result across clinical settings, which increases the generalizability of our findings. Second, our substantially larger sample size allowed stratification of results by patient age (infants 0 to 28 days vs 29 to 60 days) as well as by the presence of CSF pleocytosis.…”
Section: Discussionsupporting
confidence: 63%
“…(2015) found that use of antibiotics, invasive diagnostic tests, and hospitalization for febrile infants varied significantly 9 . Implementation of institutional clinical practice guidelines (CPGs) is associated with substantially decreased variation in care, but the specific content of these CPGs remains unstandardized 10 . Therefore, developing and disseminating standardized CPGs across a broad range of institutions could have a profound impact on the management of febrile infants nationally.…”
Section: Background and Significancementioning
confidence: 99%